Pharyngeal Microflora Disruption by Antibiotics Promotes Airway Hyperresponsiveness after Respiratory Syncytial Virus Infection - Ni, Ke (Public Library of Science, 2012)
BACKGROUND: Regulatory T cells (Treg cells), which are essential for regulation of immune response to respiratory syncytial virus (RSV) infection, are promoted by pharyngeal commensal pneumococcus. The effects of pharyngeal microflora disruption by antibiotics on airway responsiveness and relative immune responses after RSV infection have not been clarified. METHODS: Female BALB/c mice (aged 3 weeks) were infected with RSV and then treated with either oral antibiotics or oral double distilled water (ddH(2)O) from 1 d post infection (pi). Changes in pharyngeal microflora were analyzed after antibiotic treatment for 7 d and 14 d. At 8 d pi and 15 d pi, the inflammatory cells in bronchoalveolar lavage fluid (BALF) were investigated in combination with tests of pulmonary histopathology, airway hyperresponsiveness (AHR), pulmonary and splenic Treg cells responses. Pulmonary Foxp3 mRNA expression, IL-10 and TGF-β1 in BALF and lung homogenate were investigated at 15 d pi. Ovalbumin (OVA) challenge was used to induce AHR after RSV infection. RESULTS: The predominant pharyngeal commensal, Streptococcus, was cleared by antibiotic treatment for 7 d. Same change also existed after antibiotic treatment for 14 d. After RSV infection, AHR was promoted by antibiotic treatment at 15 d pi. Synchronous decreases of pulmonary Treg cells, Foxp3 mRNA and TGF-β1 were detected. Similar results were observed under OVA challenge. CONCLUSIONS: After RSV infection, antibiotic treatment cleared pharyngeal commensal bacteria such as Streptococcus, which consequently, might induce AHR and decrease pulmonary Treg cells.